Haemato-Biochemical Profile of COVID-19 Patients Hospitalized At the The Amissa Bongo Regional Hospital Center (ABRHC) in Franceville, Gabon - Ndong Mba, Thiéry; Moundounga Kenguele, Hilaire; Pambo-Pambo, Brice Arnaud (British Journal of Healthcare and Medical Research, 2022)
Taking place from 16 May to 31 August 2021, the aim of this study was to describe the haemato-biochemical profile of COVID-19 patients in 250 diagnosed individuals. With a sex ratio of 0.84, seventy-nine symptomatic COVID-19 patients, 36 of whom (45.57%) were less infected and 43 of whom (54.43%) were predominantly infected, were hospitalised at the SICOV of the CHRAB. They ranged in age from twenty-one to eighty-one years, with an average age of 45±5 years. After taking blood samples and collecting certain biological specimens for the determination of plasma electrolytes (sodium, potassium, chlorine and calcium), the analysis of the results and the estimation of the values of the haematological parameters of the interned patients revealed that one patient suffered from a hypochromic microcytic anaemia associated with thrombocytopenia. Hyperleukocytosis was found in 43% of cases, 43% of subjects had lymphopenia, 39.2% of cases had thrombocytopenia, and 63.3% had anemia. Observation of biochemical parameters revealed a uraemia rate of less than 35.89% for all 79 patients. 31.7% of patients had elevated creatinemia. 58.34% had elevated AST and ALT levels, 5% had elevated total bilirubin. Sodium (Na+=77%), potassium (K+=33%) and calcium (Ca2+=20%) levels were significantly lower, forcing the patients to develop a severe form of COVID- 19. Hypochloremia was present in 20% of these patients. While 20% hypercalcaemia was recorded in the patients, there were no cases of hypocalcaemia. Some patients suffered from co-morbidities such as renal failure and heart failure. Of the 79 patients hospitalised, 11 died (13.92%) and 68 were cured (86.08%). The risk of death was higher in patients with one or more co-morbidities. Our study shows that in patients under 58 years of age, 27.3% of the deceased patients had at least one reported co-morbidity such as diabetes (3.79%) and/or hypertension (6.28%). Key words: COVID-19, SARS-CoV-2, Hematobiochemical